ANALYSIS OF FOREIGN EXPERIENCE AND MODERN REQUIREMENTS IN DEVELOPING THE PROFESSIONAL COMPETENCE OF PROSPECTIVE PRIMARY SCHOOL TEACHERS BASED ON SMART TECHNOLOGIES (Multidisciplinary Journal of Science and Technology, 2025)
This study examines foreign experiences and contemporary educational requirements in developing the professional competence of prospective primary school teachers through the integration of smart technologies. The research analyzes international best practices in teacher education, focusing on the use of digital platforms, artificial intelligence, adaptive learning systems, and smart educational environments. Particular attention is paid to how smart technologies contribute to the formation of pedagogical, digital, methodological, and reflective competencies required of modern primary school teachers. The study also identifies current global trends and competency-based standards in teacher training, highlighting the shift toward learner-centered, technology-enhanced, and practice-oriented models of professional development. Based on the analysis, key requirements for improving teacher education programs are outlined, emphasizing sustainability, adaptability, and alignment with the demands of the digital society.